2005
DOI: 10.1088/1741-2560/2/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of motor unit number estimation techniques

Abstract: Motor unit number estimation (MUNE) is an electrodiagnostic procedure used to evaluate the number of motor axons connected to a muscle. All MUNE techniques rely on assumptions that must be fulfilled to produce a valid estimate. As there is no gold standard to compare the MUNE techniques against, we have developed a model of the relevant neuromuscular physiology and have used this model to simulate various MUNE techniques. The model allows for a quantitative analysis of candidate MUNE techniques that will hopef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…At the level of the nerve trunk, recruitment of motor axons is random in relation to axon diameter and is likely superficial within the nerve trunk (Doherty and Brown 1993;Baker et al 2000;Major and Jones 2005) as depicted in Fig. 6b.…”
Section: Temporal Aspects Of Recruitmentmentioning
confidence: 99%
“…At the level of the nerve trunk, recruitment of motor axons is random in relation to axon diameter and is likely superficial within the nerve trunk (Doherty and Brown 1993;Baker et al 2000;Major and Jones 2005) as depicted in Fig. 6b.…”
Section: Temporal Aspects Of Recruitmentmentioning
confidence: 99%
“…Factors that might be more important are the amount and density of interposed tissues and the relative depth of the motor axons in the fascicle at each location. Using a stimulation model, it was shown that preferential activation of large diameter motor axons is unlikely in MPS (Major and Jones, 2005). Additional SMUPs were selectively recruited when altering the stimulus pulse width, most likely because myelinated nerve fibers of different sizes have different thresholds (Grill and Mortimer, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The problem of alternation (motor units recruited in numerous combinations by stimulation of a motor nerve) is overcome in this method by calculating the average of 10 randomly chosen motor unit forces associated with incremental force increases at different stimulus amplitudes instead of counting incremental increases in muscle twitch force [40][41][42] .…”
Section: Motor Unit Number Estimationmentioning
confidence: 99%